Digital kids of the Heisei era: experiment at Toyonaka Bunka Kindergarten - Matsuda, Souhei (The Turkish Journal of Pediatrics, 1999)
I wonder what most people think when they hear of small children playing on computers in kindergarten.One can almost hear the responses: "Why should kindergarten children have to use computers?" Small children are using computers? It's much too early!" "At kindergarten children should be singing, playing games, and making mud pies!" A computer is the epitome of the artificial. If we really make a mess of things, humans will become slaves to computers. What can they be thinking, putting such things in kindergartens as a child's toy?Many people who think in this way have never touched a computer, and it often seems the case that these "emotional opponents" are opposed to them only because of their own preconceptions. There is still a preconception that" a computer = a square machine like a TV with lots of difficult-looking keys". Computers are now in virtually all of the electronic appliances we use every day, refrigerators, washing machines, vacuums and televisions, and we think nothing of it. We live each day using computers, but only the "square" computer invites such contempt. Why is this the case?On the other side, there are the "proactive endorsers", who think "Computers have spread thus far in society and schools, so we must let children become familiar with them from a very young age!" These people often seem to want to teach everyone everything. There is much to know about the image and use of computers. They seem to think that if adults don't teach them, children won't understand anything. On this point, they are at the same level as the "emotional opponents", in that they conceive of computers as being something out of the ordinary.